Analisis Kesulitan Belajar Mahasiswa Kategori Nilai Rendah dalam Menyelesaikan Masalah Statistika Pokok Bahasan Ukuran Tendensi Sentral, Ukuran Dispersi, dan Ukuran Letak - Mika Ambarwati; Fitri Apriyani Pratiwi (IKIP Budi Utomo Malang, 2016)
The aim of this research was to describe the analyzed difficulty learn student category of low value in solving the statistics problems on discussion size measure of central mainstream, size measure dispersi, and the size measure situation. This research used the descriptive research method with the qualitative explorative approach. The subjects of the research were 12 students 2013 A and 2013 B Program Study of Education Language and literature Indonesia, four students categoryof high value, four students category of medium value, andfour students category of low value. The instruments used to gather data of worksheet for problem solving and interview guidelines. The data were task-based interview on the learning material of statistics problems. They were validated by using the time triangulation and the reference fulfillment. The data were analyzed using a Miles and Huberman’s concept, that was data reduction, presentation, and conclusion. The results of the research are as follows. 1) Students categoryof low value not difficulties determining concept, using formula, and calculate solving the statistics problems on discussion size measure of central mainstream. 2) Students categoryof low valuedifficulties determining concept, using formula, and calculate solving the statistics problems on discussion size measure dispersicharacteristic coefficient of variation and permanent deviasi. 3) Students categoryof low valuedifficulties determining concept, using formula, and calculate solving the statistics problems on discussion size measure situationcharacteristic kuartilconcept from data pertain.